2016
DOI: 10.1016/j.ajog.2015.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Cervical pessary placement for prevention of preterm birth in unselected twin pregnancies: a randomized controlled trial

Abstract: In women with twin pregnancy, routine treatment with cervical pessary does not reduce the rate of spontaneous early preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 25 publications
6
137
3
6
Order By: Relevance
“…A preliminary result confirmed that 2-year neonatal survival in the pessary group was higher than that in the group that was managed expectantly. The second RCT in unselected twin pregnancies by Nicolaides et al could not confirm these results 7 . In their study, the cervical pessary was removed < 34 weeks in 22.3% of pregnancies; however, they did not report the gestational week (or range) at delivery in this group of patients.…”
contrasting
confidence: 44%
See 1 more Smart Citation
“…A preliminary result confirmed that 2-year neonatal survival in the pessary group was higher than that in the group that was managed expectantly. The second RCT in unselected twin pregnancies by Nicolaides et al could not confirm these results 7 . In their study, the cervical pessary was removed < 34 weeks in 22.3% of pregnancies; however, they did not report the gestational week (or range) at delivery in this group of patients.…”
contrasting
confidence: 44%
“…To our knowledge, three randomized controlled trials (RCTs) on pessary use in twin pregnancy have been published. Two of the studies found that cervical pessary did not reduce the rate of PTB in unselected twin pregnancies 6,7 ; the rate did not differ between women allocated to a pessary or no pessary group. However, in the study by Liem et al 6 , the rate of PTB < 34 weeks was reported as 14% in women with a CL < 38 mm at 22 weeks who received pessary placement, compared to nearly 30% in a matched short-CL control group.…”
mentioning
confidence: 99%
“…Pessary use was also associated with less children born with a birth weight <2,500 g (RR 0.72; 95% CI 0.54–0.97). Another recent trial, by Nicolaides et al,82 including 1,180 twin pregnancies without a specific cervical length cutoff, showed no effect of a cervical pessary on PTB rates <34 weeks (RR 1.05; 95% CI 0.79–1.4) and adverse neonatal outcome (RR 1.09; 95% CI 0.85–1.4). The post hoc analysis evaluating 214 women with a short cervix (<25 mm) did not change these results.…”
Section: Prevention Of Ptbmentioning
confidence: 98%
“…124 Finally, there is recent evidence that cervical pessary may decrease the likelihood of preterm birth in women with twin pregnancies. 36, 125129 Thus, the improved prediction of PTB using serial measurement of CL may facilitate treatment with progesterone if more evidence becomes available to support the use of progesterone in that context. 22, 26, 66, 124, 130, 131 Still, it should be emphasized that there is currently no level-I evidence that routine monitoring of cervical length in women with twin pregnancies improves pregnancy outcome, 132 and therefore current recommendations do not support such a practice.…”
Section: Commentsmentioning
confidence: 99%